2018
DOI: 10.1111/jdv.15243
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of a new ex vivo confocal laser scanning microscope compared to H&E‐stained paraffin slides for micrographic surgery of basal cell carcinoma

Abstract: Confocal laser scanning microscopy is a time-saving and very effective alternative to classical paraffin-embedded or frozen sections. Patient treatment could be improved due to shorter hospital stays or faster outpatient therapy due to reduced intervals between surgical stages. Diagnostic accuracy of the microscope used still must be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 33 publications
(86 reference statements)
3
36
0
7
Order By: Relevance
“…Learning curves for confocal laser scanning microscopy have been described elsewhere [13, 16, 23, 24]. Even though investigators needed only a two‐day introduction to use the appliance with confidence, we did notice that image quality improved over the course of our study, and there was a trend towards requiring shorter periods of time.…”
Section: Discussionmentioning
confidence: 71%
“…Learning curves for confocal laser scanning microscopy have been described elsewhere [13, 16, 23, 24]. Even though investigators needed only a two‐day introduction to use the appliance with confidence, we did notice that image quality improved over the course of our study, and there was a trend towards requiring shorter periods of time.…”
Section: Discussionmentioning
confidence: 71%
“…Different staining methods have been used to enhance the contrast of cell structures in ex vivo CM with no damage to conventional histopathology preparation (Table 3). 14,17,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Correlation of ex vivo confocal microscopy and normal skin histology Ex vivo confocal images allow a good correlation with conventional histology with H&E ( Figure 2). In a recent study by Sch€ u€ urmann et al, 38 using the VivaScope V2500, they found that the following cutaneous and subcutaneous structures are excellently displayed in the images, with only minimal differences compared with H&E slides: every layer of the epidermis, collagen and elastic tissue; lymphatic and capillary vessels; hair follicles and other skin appendages; eccrine and sebaceous glands; subcutaneous fat; elastic cartilage and muscle fibres.…”
Section: Technologymentioning
confidence: 99%
“…23 In a recent study with an FCM device with different samples from punch biopsies from Mohs specimens, Peters et al reported a median total time to generate and evaluate a Basal cell carcinoma, 24,[43][44][45][46][47] squamous cell carcinoma, 26,45,[48][49][50] dermatofibrosarcoma, 41 melanocytic lesions, 35,51,52,[54][55][56]77 tumours in special sites 55,62,78 (eyelid tumours, tumours of the conjunctiva, tumours of the nails) Other tumours: breast, prostate, brain, thyroid, oesophagus, stomach, colon, lung, lymph node, cervix, oral mucosa and larynx [69][70][71][72] Diagnosis of infections: mucormycosis, 63 dermatophytosis, 64 herpes virus, 65 molluscum contagiousm, 66 aspergillosis 79 Inflammatory skin diseases 36,37,68 (vasculitis, bullous diseases, psoriasis, lichen planus, discoid lupus erythematosus) Skin fillers 67 confocal laser scanning microscopy (CLSM) image of 5Á17 min (range 2Á05-20Á17). 34 Most of the ex vivo CM studies were conducted on BCCs. Subsequently, this technique has been used for other epithelial tumours, melanocytic tumours, dermatofibrosarcoma and Paget disease.…”
Section: Ex Vivo Confocal Microscopy For the Evaluation Of Resection mentioning
confidence: 99%
See 2 more Smart Citations